Complete blood count test in the evaluation of anemia: More than a screening test? (Annals of Medical Research, 2021)
Aim: Anemia is defined as a reduction in the red blood cell mass or blood hemoglobin concentration. Complete blood count (CBC) analyses provide comprehensive information with regard to the classification of anemia. We aimed to determine the prevalence and remind the possible etiologies of anemia in our province using CBC analyses.Material and Methods: This retrospective study was conducted in a secondary healthcare center in northern Turkey. A total of 2578 healthy children enrolled. Their sociodemographic features, clinical history, and CBC results were retrospectively reviewed from the hospital records. According to CBC analyses, hemoglobin (HGB), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), mean corpuscular hemoglobin (MCH) and red cell distribution width (RDW) levels were evaluated.Results: The prevalence of anemia in the whole study population was 27.6% (n=713). When stratified according to the age subgroups of the study, the prevalances varied between 21.3% and 41.2%. Among the anemic patients, 42.9% (n=306) had microcytic, 56.1% (n=400) had normocytic and 1% (n=7) had macrocytic anemia Conclusion: The prevalance of anemia was >20% in all the age groups, revealing that anemia is a significant public health problem in our province. Detailed analysis of the CBC provides comprehensive information regarding the classification of anemia. It saves time and money for well−child follow up by facilitating the direct application of etiologic tests.
Keywords: Anemia; complete blood count, well-child